Value of CT–PET after neoadjuvant chemoradiation in the prediction of histological tumour regression, nodal status and survival in oesophageal adenocarcinoma. Issue 13 (28th October 2014) - Elliott, J A; O'Farrell, N J; King, S; Halpenny, D; Malik, V; Muldoon, C; Johnston, C; Reynolds, J V
Abstract: Background: The role of CT–PET after neoadjuvant chemoradiation (nCRT) for prediction of pathological response and oncological outcome in oesophageal and junctional adenocarcinoma (OAC) is unclear. The relationship between complete metabolic response (cMR), pathological complete response (pCR) and nodal status has not been clarified. Methods: Patients with locally advanced OAC selected to receive nCRT and surgery with curative intent, on the basis of staging that included CT–PET positivity, were included. Repeat scanning (PET2) with an identical protocol was performed 2–4 weeks after completion of nCRT (cisplatin and 5-fluorouracil plus 44 Gy radiation). Changes in [ 18 F]fluorodeoxyglucose uptake, considered as either a maximum standardized uptake value (SUVmax) or a relative reduction (%ΔSUVmax), and PET-predicted nodal status following nCRT were compared with histopathological response, histological node positivity and survival. Results: One hundred consecutive patients with PET-positive OAC were studied. Following nCRT, PET2 identified M1 disease in 2·0 per cent of patients. There were no significant associations between PET2 SUVmax or %ΔSUVmax with respect to primary tumour stage (ypT) ( P = 0.216 and P = 0·975 respectively), tumour regression grade ( P = 0·109 and P = 0·232), pCR ( P = 0·633 and P = 0·870) or complete resection (R0) ( P = 0·440 and P = 0·235). The sensitivity of PET2 for ypN was 10 per cent. %ΔSUVmax was not associated with disease-free or overall survival ( P = 0·162 and P = 0·154 respectively). Of 46 patients with a cMR on PET2, 37 (80 per cent) had histological evidence of residual tumour in the resected specimen, and cMR was not associated with overall survival benefit ( P = 0·478). Conclusion: CT–PET following nCRT for OAC has poor prognostic and discriminatory value for clinical application. Abstract : Unreliable after chemoradiotherapy